Human genome editing in clinical applications: Japanese lay and expert attitudes - Sawai, Tsutomu; Hatta, Taichi; Akatsuka, Kyoko; Fujita, Misao (Frontiers in Genetics, 2023)
Background: The world’s first gene-edited babies, reported by the Chinese scientist He Jiankui, prompted an outcry of criticism and concerns worldwide over the use of genome editing for reproductive purposes. Many countries and academic associations opposed to heritable genome editing (HGE) called for public discussion involving various stakeholders. To hold a discussion of this nature and form a consensus concerning HGE, we must understand under what conditions stakeholders consider HGE acceptable and the reasons for which they deem it unacceptable. Methods: Laypeople and researchers were surveyed in May 2019. They were asked about the degree of their acceptance toward somatic genome editing (SGE) and HGE; those who answered “acceptable depending on the purpose” were queried further regarding their acceptance in the contexts of specific clinical purposes. Results: Responses were obtained from 4,424 laypeople and 98 researchers. The percentage of respondents choosing each option in attitudes to HGE was, from largest to smallest: “acceptable depending on purpose” (laypeople 49.3%; researchers 56.1%), “not acceptable for any purpose” (laypeople 45.8%; researchers 40.8%), and “acceptable for any purpose” (laypeople 5.0%; researchers 3.1%). In an additional question for those who answered “acceptable depending on the purpose,” laypeople found the following purposes acceptable: infertility treatment (54.5%), treatment of life-threatening diseases (52.2%), and treatment of debilitating diseases (51.4%). Meanwhile, the degree of acceptance for enhancement purposes was 10.7, 7.9, 6.2, and 5.5% for physical, cognitive, health, and personality enhancements, respectively. In contrast, acceptance among the researchers was 94.5% and 92.7% for the treatment of life-threatening and debilitating diseases, respectively, compared with 69.1% for infertility treatment. Researchers’ acceptance for enhancement purposes was similar to that of the lay participants, with 12.7, 9.1, 10.9, and 5.5% for physical, cognitive, health, and personality enhancement, respectively. Conclusion: In the past, debates regarding the acceptability of human genome editing in clinical applications tend to focus on HGE in many countries. Society will now need to debate the acceptability of both types of human genome editing, HGE and SGE.